(untitled) (Al-Qamar, 2023)
Child sexual abuse is a prevalent issue in developing countries, including Pakistan and its ubiquity has risen steadily over the years. Children, the most vulnerable segment of our society, must be educated and empowered to defend themselves against victimization by strangers, their family members, and teachers, especially in this age of globalization. In developed countries, the government is responsible to protect its citizens from such physical assault. Children who have suffered such abuse cannot develop normally on mental and psychological scale. This paper analyses the psychological implications of child sexual abuse in Pakistan with a special emphasis on the need for augmented legal and legislative procedures to expedite the administration of justice in such cases.